Numerical Simulation of Fracture Failure in Three-Point Bending Specimens of Yellow River Granular Ice - Yu Deng; Ju Liang; Juan Wang (Crystals)
Currently, a comprehensive understanding of the macro- and micro-scale mechanisms of ice fracture failure in the Yellow River remains limited. Therefore, this paper adopts a microscopic perspective by modeling Yellow River granular ice as a three-phase composite comprising ice grains, grain boundaries, and initial defects. A numerical approach was proposed to simulate river ice fracture using a three-dimensional random defect solid element model, accompanied by the development of an elastic–brittle constitutive model for Yellow River granular ice. The fracture process of three-point bending samples of Yellow River granular ice was numerically simulated. The results indicated that the crack locations and failure progression in the simulations aligned well with observations from physical tests. Furthermore, the numerical analysis yielded values that aligned closely with those from the physical tests. The comparison with physical tests confirms that the proposed model effectively simulates the three-point bending fracture process of river ice. These findings provide valuable insights for the numerical simulation of fracture behavior in Yellow River granular ice.